Economic Evaluation of ART and Hall in Primary Molars - Mariana Pinheiro de Araujo; Jonathan Rafael Garbim; Nicola Patricia Innes; Daniela Hesse; Clarissa Calil Bonifácio; Isabel Cristina Olegário; Mariana Minatel Braga; Fausto Medeiros Mendes; Daniela Prócida Raggio (BMC Oral Health)
Abstract Background This study reports an economic evaluation from the perspective of the Brazilian healthcare system. This is a secondary outcome of a three-year randomised controlled trial that compared Atraumatic Restorative Treatment (ART) to the Hall Technique (HT) for managing occluso-proximal caries lesions in primary molars. The primary outcome showed that the HT had a higher survival rate compared to ART and the economic evaluation was to test cost-effectiveness. Methods Children (5–10 years old) in public schools of Tietê-SP/Brazil, were randomly allocated to either the ART or HT arm. Treatment survival was assessed using Kaplan-Meier analysis. The economic evaluation considered baseline and cumulative material and professional costs based on the Brazilian National Health System (SUS) perspective. For the economic analysis, direct and indirect costs were collected and calculated. When retreatment was necessary, an incremental cost of only one retreatment per child was considered for the analysis. All costs were collected in reais and converted and reported in euros. A discount rate of 5% was considered and a bootstrap regression was used to assess material costs’ dynamics over time (α = 5%). Monte-Carlo simulation generated cost-effectiveness scatter plots. Results The study included 131 participants (ART = 65; HT = 66) and 112 (85.5%) were followed up over three years. Survival was higher in HT compared to ART restorations (ART = 32.7%; HT = 93.4% p < 0.001). The HT (€13.02) cost less compared to ART (€16.79) (p < 0.001 95% CI: -10.07 to -1.87) due to ART higher treatment failure and cumulative costs. Although baseline costs were lower in the ART group, the cumulative cost due to the need for restoration replacement was higher after 3 years. Conclusion Hall Technique is a cost-effective strategy compared to Atraumatic Restorative Treatment for managing occluso-proximal carious lesions in primary molars in a school setting after 36 months, particularly from the perspective of the Brazilian public health system. Trial registration This trial was registered in ClinicalTrials.gov (NCT02569047) on 2015-10-06.